The Many Facets of SDF-1α, CXCR4 Agonists and Antagonists on Hematopoietic Progenitor Cells. (23rd April 2007) - Faber, Anne; Roderburg, Christoph; Wein, Frederik; Saffrich, Rainer; Seckinger, Anja; Horsch, Kerstin; Diehlmann, Anke; Wong, Donald; Bridger, Gary; Eckstein, Volker; Ho, Anthony D.; Wagner, Wolfgang
Abstract : Stromal cell-derived factor-1alpha (SDF-1α ) has pleiotropic effects on hematopoietic progenitor cells (HPCs). We have monitored podia formation, migration, proliferation, and cell-cell adhesion of human HPC under the influence of SDF-1α, a peptide agonist of CXCR4 (CTCE-0214), a peptide antagonist (CTCE-9908), and a nonpeptide antagonist (AMD3100). Whereas SDF-1α induced migration ofCD 34 + cells in a dose-dependent manner, CTCE-0214, CTCE-9908, and AMD3100 did not induce chemotaxis in this concentration range albeit the peptides CTCE-0214 and CTCE-9908 increased podia formation. Cell-cell adhesion of HPC to human mesenchymal stromal cells was impaired by the addition of SDF-1α, CTCE-0214, and AMD3100. Proliferation was not affected by SDF-1α or its analogs. Surface antigen detection of CXCR4 was reduced upon treatment with SDF-1α or AMD3100 and it was enhanced by CTCE-9908. Despite the fact that all these molecules target the same CXCR4 receptor, CXCR4 agonists and antagonists have selective effects on different functions of the natural molecule.